ANALYSIS OF THE POTENTIAL OF RUBBER FARMING AND PALM OIL FARMING IN REGIONAL ORIGINAL INCOME IN WEST KALIMANTAN 2019-2021 PERIOD - Marhamah Marhamah (Journal of Agriculture, 2023)
The diversity of wealth in Indonesia makes Indonesia one of the countries that has the largest type of agriculture in the world. Rubber farming is a long-term type of crop that is capable of being a main source of income and can even contribute to the processing of goods on an international scale, as well as oil palm is a new type of farming income, which has become the hottest spotlight among farmers and entrepreneurs as income has shot up. tall. So that here makes a comparison between rubber and oil palm income by the people of Retok Sungai Segak, Sebangki sub-district, Landak Regency as a future reference that can be more dominant in the rubber or palm business, this will become a reference material for the community managing the business. Not closing this will be a problem for people who persist in one option or both continue to operate. This research is an analysis of the income of rubber farming and oil palm farming which is expected to introduce knowledge to the Retok community to choose or both continue.